KNOWLEDGE AS AN INSTRUMENT OF HUMAN ACTIVITY - Скиба, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the problem of instrumental knowledge research.